Between local and standard varieties: horizontal and vertical convergence and divergence of dialects in Southern Spain - Villena-Ponsoda, Juan Andrés; Ávila-Muñoz, Antonio Manuel; Vida-Castro, Matilde Ángeles; Von-Essen, María Clara (My University, 2015)
El objeto de esta comunicación es presentar los procesos de convergencia y divergencia horizontal y vertical en los dialectos innovadores del español meridional.
Keywords: Español - Andalucía; Sociolingüística; Variación lingüística; Convergencia y divergencia dialectal; Nivelación dialectal